2016
DOI: 10.1016/j.jinf.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytokine responses against novel Mtb antigens as diagnostic markers for TB disease

Abstract: A biosignature of 6 cytokines obtained after stimulation with four Mtb antigens has moderate potential as a diagnostic tool for pulmonary TB disease individuals and stimulated marker expression had no added value to unstimulated marker performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…However, the highest discriminative biomarker set was a complex co-expression of serum IL-18BP and IL-37 and IP-10 and IFN-γ, which may be useful in the rapid differentiation between ATB patients and LTBI individuals. Our data are consistent with the opinion that a complex biomarker panel is more robust than single markers for TB screening [57,26]. The set of seven serum biosignatures, comprised of apolipoprotein-A1, CRP, complement factor H, IFN-γ, IP-10, serum amyloid A and transthyretin, and a panel of five other serum biomarkers, including IFN-γ, IL-6, IL-18, CRP and MIG, showed potential in screening for TB in African countries endemic for HIV infection [8,27].…”
Section: Discussionsupporting
confidence: 91%
“…However, the highest discriminative biomarker set was a complex co-expression of serum IL-18BP and IL-37 and IP-10 and IFN-γ, which may be useful in the rapid differentiation between ATB patients and LTBI individuals. Our data are consistent with the opinion that a complex biomarker panel is more robust than single markers for TB screening [57,26]. The set of seven serum biosignatures, comprised of apolipoprotein-A1, CRP, complement factor H, IFN-γ, IP-10, serum amyloid A and transthyretin, and a panel of five other serum biomarkers, including IFN-γ, IL-6, IL-18, CRP and MIG, showed potential in screening for TB in African countries endemic for HIV infection [8,27].…”
Section: Discussionsupporting
confidence: 91%
“…CD107a was added to each well (to a final concentration of 0.2%) and the plate incubated for 15–16 h at 37°C, 5% CO 2 . The concentrations of PPD and EC, as well as the duration of stimulation, have been previously validated in our laboratory and by other groups ( 47 53 ). Subsequently, 1X protein transport inhibitor (eBioscience, UK) was added and incubation continued for a further 3 hrs.…”
Section: Methodsmentioning
confidence: 94%
“…In addition to conforming the data previously published for a Chinese population (Cai et al) in 4 different TB cohorts, we also showed the specificity for TB disease in comparison to clinically important differential diagnoses, such as sarcoidosis and pneumonia. As C1q is produced by cells of monocytic origin, it reflects another component of the immune space compared to most currently applied TB biomarkers, such as C-reactive protein and IP-10 ( 44 47 ). In addition, C1q levels are technically easy to measure and the C1q protein is not sensitive to degradation.…”
Section: Discussionmentioning
confidence: 99%